THE ASSESSMENT OF DIAGNOSTIC AND PROGNOSTIC VALUE OF IMMUNOLOGIC BIOMARKERS IN PATIENTS WITH MYOCARDITIS - Gavrilenko, T.I.; Cherniuk, S.V.; Pidgaina, O.A.; Ryzhkova, N.A.; Yakushko, L.V. (World of Medicine and Biology, 2019)
Background. Study of diagnostic and prognostic role of immunologic biomarkers in patients with myocarditis might be useful for prediction of disease clinical course and risk stratification as also for timely correction of patient management. The aim of the study was to establish immunologic biomarkers of the heart structural and functional impairment and heart failure persistence in patients with myocarditis. Material and methods. We studied 70 patients with acute myocarditis and heart failure II or above NYHA class and left ventricular (LV) ejection fraction (EF) ≤ 40%. The examination was performed in the 1-st month from the disease onset and after 12 months of follow-up. All patients underwent for the assessment of immunologic parameters, 2D-echocardiography and cardiac magnetic resonance imaging (MRI). Statistic analysis was performed by the use of Exсel XP (Місrosoft Office, USA) and Statistica for Windows v. 6.0 (Statsoft, USA) software. Results. It was established that in the debut of the disease myocarditis is characterized by the presence of active inflammatory changes in the myocardium, which were detected by cardiac magnetic resonance imaging and accompanied by the activation of immunopathological reactions of cell and humoral type, synthesis of effector T- lymphocytes, anti-myocardial antibodies and proinflammatory cytokines, which caused dilatation and systolic LV dysfunction. The high content of anti-myosin antibodies (≥ 3,0 opt. sq. units) and antibodies to β1-adrenergic receptors (≥ 0,35 opt. sq. units) оn the 1-st month from the onset of myocarditis was associated with active inflammatory changes of the myocardium (oedema and hyperemia) after 12 months of follow-up and high activity of sensitized to myocardium T-lymphocytes (≥ 7,0 %) in the 1-st month from the debut of myocarditis was followed by the presence of LV systolic dysfunction (EF ≤ 40%) after 12 months. The obtained cut-off values of immunologic biomarkers may be useful in clinical practice for the early prediction of myocarditis clinical course, persistence of myocardial inflammation and LV systolic dysfunction in patients with myocarditis after 12 months of follow-up. Conclusion. We detected early immunologic predictors that in the first month after disease onset could be used for prediction of the heart structural and functional impairment and heart failure persistence in patients with myocarditis after 12 months of observation: serum level of anti-myosin antibodies, antibodies to β1-adrenergic receptors and activity of sensitized to myocardium T-lymphocytes.
Keywords: myocarditis; immune state; antibodies to myocardium; morphofunctional condition of heart